Non-Hodgkin's lymphoma in the practice of the family doctor (clinical observation). - I. V. Vasylevska (Medičnì Perspektivi)
There is presented a clinical observation on the problem of establishing an oncological diagnosis by a family doctor, the route to a doctor-oncologist for specific treatment with subsequent work in the brigade team and medical support during the course of chemotherapy for the prevention and timely elimination of side effects and complications.